UPPER DEVONIAN CONODONT BIOSTRATIGRAPHY OF SHAMS ABAD SECTION, KERMAN PROVINCE, IRAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The study of the conodont fauna from the Upper Devonian Shams Abad section provides new data on the stratigraphy of the Bahram Formation in the Kerman province, in southeastern Iran. The fauna includes twenty-four species, mainly belonging to genera Polygnathus and Icriodus, and gives evidence of a late Frasnian to middle Famennian age, in contrast to previous interpretation of the same unit. The shallow water conodont biofacies confirms an inner shelf to foreshore shallow marine depositional environment.
Keywords: Frasnian; Famennian; Conodonts; Biostratigraphy; Bahram Fm.; Shams Abad; Kerman Province; Iran